(untitled) (Proceedings of the World Conference on Children and Youth, 2021)
This qualitative descriptive study has examined a Child Friendly School (CFS) model visà-vis the Confucian philosophy in the Philippine education setting. CFS model is a child-centered framework curriculum design that is considered to be of western thought and which espouses a holistic philosophy of an inclusive, healthy and protective school environment for children. The contextualized adoption of CFS in one of the elementary public schools was examined through the Confucian tenets of a moral, holistic and self-actualized learning. This contextualization can have mismatch or misalignment especially on a case where the system was developed outside of the locale, such as the case of CFS. Thus, this paper has explored a child-friendly school in terms of its curriculum, practices, school policies and integrated programs that corresponds to the core elements of a CFS model in the case of Iraya Elementary School. Specifically, it responded to the questions: what are the features of Child Friendly School model that relates to a Confucian philosophy of education? What are the Child Friendly School practices of Iraya Elementary School? How is the Confucian philosophy reflected in the Child Friendly School practices of Iraya Elementary School? Data were gathered through survey, key informant interview and document analysis to examine how the Confucian philosophy of education is reflected in the CFS model. We concluded that although CFS originated from the west and Confucianism from the east, there exists congenial principles. The development of a whole child is an output of CFS with the Confucianism idea of perfection of a learner. Furthermore, the CFS upholds that education is a right and Confucius believes that everyone is educable and perfectible.